2004
DOI: 10.1017/s148180350000960x
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of acetylsalicylic acid for acute coronary syndromes in the emergency department

Abstract: Objective: Acetylsalicylic acid (ASA) is a simple and cost-effective treatment for acute coronary syndromes (ACS). Our objectives were to determine the frequency of ASA administration in the emergency department (ED) for patients with acute myocardial infarction or unstable angina, and to identify patient characteristics associated with its administration. Methods: This is a retrospective chart review of patients discharged with a final diagnosis of ACS. Data on age, gender, mode of presentation, presence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Whatever the reasons, considerable evidence suggests that individuals often fail to use medical services that have been proven effective and to offer large benefits relative to the costs (Cokkinides et al 2003;Dufresne et al 2004;Iba et al 2006;Ibrahim and Kwoh 2000;Krumholz et al 1998;McGlynn et al 2003;Stafford and Radley 2003). This underutilization can occur at any number of points in the process of providing appropriate medical care.…”
Section: Issue 3: Flaws In Decision Makingmentioning
confidence: 99%
“…Whatever the reasons, considerable evidence suggests that individuals often fail to use medical services that have been proven effective and to offer large benefits relative to the costs (Cokkinides et al 2003;Dufresne et al 2004;Iba et al 2006;Ibrahim and Kwoh 2000;Krumholz et al 1998;McGlynn et al 2003;Stafford and Radley 2003). This underutilization can occur at any number of points in the process of providing appropriate medical care.…”
Section: Issue 3: Flaws In Decision Makingmentioning
confidence: 99%
“…6 Development and validation of a compact on-person storage device (SMHeartCard) for emergency access to acetylsalicylic acid and nitroglycerin OPEN Research An audit of a Canadian hospital showed that, among patients presenting with acute coronary syndromes (myocardial infarction or unstable angina), the median time to ASA and nitroglycerin administration was more than 90 minutes after arrival at the emergency department. 7 About 30% of people with myocardial infarction do not survive long enough to reach medical care, 8 and this is more frequent in people who live and work in geographically isolated areas.…”
mentioning
confidence: 99%